Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T21:18:33+01:00
A) 6*(x-2)= -54
6x-12=-54
6x=-54+12
6x= -42 / :6
x= -7
b)1/2 (a+4)=6
1/2a+2=6
1/2a=6-2
1/2a=4 / * 2
a=8
c)1/4(x-8)= -22
1/4x-2=-22
1/4x=-22+2
1/4x=-20 / * 4
x=-80
d)(-3)*(x+2)= -12
-3x-6=-12
-3x=-12+6
-3x=-6/*-1
3x=6 / :3
x=2
Licze na naj!

2010-03-15T21:19:25+01:00
A) 6*(x-2)= -54
6x-12 = -54
6x = -54+12
6x = -42 / :6
x = -7

b)1/2 (a+4)=6
1/2 a + 2 = 6
1/2 a = 6-2
1/2 a = 4 / *2
a = 8

c)1/4(x-8)= -22
1/4 x - 2 = -22
1/4 x = -22+2
1/4 x = -20 / *4
x = - 80

d)(-3)*(x+2)= -12
-3x-6 = -12
-3x = -12+6
-3x = -6 / :(-3)
x = 2